How Did Tour Guide Survive during the Covid-19 Pandemic? A Study on The Roles of Self-Efficacy and Organizational Commitment among Tour Guides in Bali - I Dewa Ayu Nindya Prathiwi S; Ni Ketut Wiwiek Agustina (Universitas Gadjah Mada, 2023)
Tour guides are a fundamental part of the tourism industry, which has been seriously affected by the COVID-19 pandemic. Tour guides are expected to find alternatives to survive because of fluctuations over 50% decline in tourism. The pre-pandemic and post pandemic times have significantly impacted the employment of tour guides including those in Bali. In this disruption period, how did tour guide manage to survive? This quantitative research aims to understand the survival mechanism of tour guides by examining whether self-efficacy has a relationship with the organizational commitment of active tour guides in a travel agency in Bali, especially when mediated by job satisfaction. This research uses Structural Equation Model Partial Least Square (SEM-PLS) technique to analyze the research problem. The population in this study were active tour guides in a travel agency in Bali. The sampling techniqueuses a saturated sample. Direct hypothesis analysis found that: (1) Self-efficacy has a significant positive relationship to organizational commitment. (2) Self-efficacy has a significant positive relationship to job satisfaction. (3) Job satisfaction has a significant positive relationship to organizational commitment. Indirect hypothesis analysis found (4) Self-efficacy and organizational commitment have a significant positive relationship mediated by job satisfaction.Age and gender as control variables have no relationship to organizational commitment. It can be concluded that selfefficacy and organizational commitment can help tour guides to survive in challenging period.